Amerykańskie obrazy w pamięci Wojciecha Karpińskiego w kontekście badań neurologicznych Antonio Damasio - Trygar, Barbara (Załącznik Kulturoznawczy, 2020)
In this article, I describe the way in which images come into being in the mind of the protagonist of the book W Central Parku [In Central Park] by Wojciech Karpiński. I analyze the protagonist’s behavior in the perspective of Antonio Damasio’s neurobiological research. Memory is one of the factors that participate in the creation of images in the artist’s mind. It is a dynamic phenomenon that collects memories evoked by various stimuli. It also participates in the creation of the autobiographical ‘self’ of the protagonist.